The pleasure of finding things out [compact disc, unabridged] : the best short works of Richard P. Feynman - Feynman, Richard P. (Richard Phillips), 1918-1988 (Blackstone Audio, 2013)
The Pleasure of Finding Things Out is a magnificent treasury of the best short works of Richard P. Feynman, from interviews and speeches to lectures and printed articles. A sweeping, wide-ranging collection, it presents an intimate and fascinating view of a life in science--a life like no other. From his ruminations on science in our culture to his Nobel Prize acceptance speech, this book will delight anyone interested in the world of ideas.